16 Acute stent thrombosis resulting in ST elevation myocardial infarction (STEMI) is associated with worse clinical outcomes than STEMI due to native coronary thrombosis. (9th June 2011) - Sammut, E C; Graham, A; Jones, D A; Rathod, K; May, S; Jain, A; Mohiddin, S; Knight, C; Mathur, A; Wragg, A
Abstract : Background: Stent thrombosis (ST) is a recognised cause of ST Elevation Myocardial infarction (STEMI) in patients with previous percutaneous coronary interventions (PCI). The incidence is increasing and to date outcomes are not well characterised, though there is a suggestion that there is a worse clinical outcome. We therefore sought to compare STEMI caused by ST vs de novo coronary thrombosis to evaluate procedural risk and clinical outcome. Methods: Clinical information was analysed from a prospective database on 2421 patients who underwent Primary PCI following STEMI between October 2003 and May 2010 at a London centre. Information was entered at the time of procedure, diagnosis of stent thrombosis made at the time by primary operator and outcome assessed by all-cause mortality information provided by the Office of National Statistics via the BCIS CCAD national audit. Results: Stent thrombosis (ST) accounted for 7.4% (180/2421) of all STEMIs with a frequency that has increased over time (5.4% in 2005 to 9.8% 2009). ST occurred early (0–30 days) in 36% (65/180), late (30 days–1 year) in 22% (40/180) and very late (>1 year) in 42% (75/180) of pts. Drug-eluting stents (DES) accounted for 48% of ST overall and 70% over the past 3 years. Proposed mechanisms included premature discontinuation of anti-platelets (11%), under-deployment of previous stent insertion (22%) and underlying prothrombotic conditions (eg, SLE) (6%). Pts with ST compared to native artery occlusion had higher rates of previous MI (53.9% vs 11%, p<0.0001) and incidence of multi-vessel disease (59.8% vs 51.7%, p=0.04 There was no difference in age, diabetes or cardiogenic shock. See Abstract 16 table 1 . Infarct size based on peak enzyme markers was similar (2.5 vs 2.2, p=0.45). In patients with ST, angiographic success (postprocedural Thrombolysis In Myocardial Infarction grade III flow) was worse than in patients with de novo STEMI (87.2% vs 93.7%, p=0.02). Pts with STEMI due to ST had higher in-hospital MACE (11% vs 3%, p=0.0001), MACE at 30 days (19% vs 6%, p<0.0001), this persisted up to 3 years (41% vs 12%, p<0.0001). See Abstract 16 figure 1 . MACE was driven by higher rates of MI (7% vs 2%, p<0.0001), TVR (14% vs 3%, p<0.0001) and death (18% vs 6%, p=0.0001). After adjusting for comorbidities, stent thrombosis was an independent predictor of long-term adverse outcome (OR=2.1, 95% CI=1.3 to 2.8, p<0.001). Conclusion: Primary PCI for treatment of ST is less effective, and these patients are at increased risk for in-hospital and long-term mortality compared with patients undergoing primary PCI due to de novo STEMI.